2004
DOI: 10.1637/7074
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of Chickens with VP2 Protein of Infectious Bursal Disease Virus Expressed in Arabidopsis thaliana

Abstract: Transgenic plants represent a safe, effective, and inexpensive way to produce vaccines. The immunogenicity of VP2 protein of an infectious bursal disease (IBD) virus variant E isolate expressed in transgenic Arabidopsis thaliana was compared with a commercial vaccine in specific-pathogen-free broiler chickens. The VP2 coding sequence was isolated and integrated into A. thaliana genome by Agrobacterium tumefaciens-mediated transformation. Soluble VP2 expressed in transgenic plants was used to immunize chickens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Denatured VP2 does not induce protection in chickens (Fahey et al, 1989), and denatured and renatured VP2 also lost the ability to induce neutralizing antibodies in chickens (Ö ppling et al, 1989). Different expression systems have been used, such as Escherichia coli (Rong et al, 2007), yeast (Fahey et al, 1991), fowlpoxvirus (Bayliss et al, 1991;Heine & Boyle, 1993), baculovirus (Vakharia et al, 1993), Semliki Forest virus (Phenix et al, 2001), and even plant expression systems (Wu et al, 2004). Either the VP2 encoding region alone or the polyprotein gene was used for expression, and polyhistidine tags have been used for effective protein purification.…”
Section: Introductionmentioning
confidence: 99%
“…Denatured VP2 does not induce protection in chickens (Fahey et al, 1989), and denatured and renatured VP2 also lost the ability to induce neutralizing antibodies in chickens (Ö ppling et al, 1989). Different expression systems have been used, such as Escherichia coli (Rong et al, 2007), yeast (Fahey et al, 1991), fowlpoxvirus (Bayliss et al, 1991;Heine & Boyle, 1993), baculovirus (Vakharia et al, 1993), Semliki Forest virus (Phenix et al, 2001), and even plant expression systems (Wu et al, 2004). Either the VP2 encoding region alone or the polyprotein gene was used for expression, and polyhistidine tags have been used for effective protein purification.…”
Section: Introductionmentioning
confidence: 99%
“…Plant-expressed proteins from infectious bursal disease virus and avian reovirus were previously tested successfully in chicken (29,30,31). The expression of influenza A virus antigen using plants was demonstrated recently, and protective efficacy has been investigated with mouse and ferret models (7,19,20).…”
mentioning
confidence: 99%
“…However, vaccines were administered by injection and also required purification steps (Farrance et al, 2011). It has been suggested that the use of plant- based oral vaccines for booster immunization, with injected vaccination for primary immunization, may be more effective than current strategies (Wu et al, 2004;Thanavala et al, 2005). Here we present data on the evaluation of efficacy, especially infection-preventing effectiveness, of a plant-based oral vaccine against protozoan infectious disease.…”
Section: Discussionmentioning
confidence: 99%